Appetite and energy intake responses to breakfast consumption and carbohydrate supplementation in hypoxia. (1st April 2020) - Griffiths, Alex; Deighton, Kevin; Shannon, Oliver M.; Boos, Chris; Rowe, Joshua; Matu, Jamie; King, Roderick; O'Hara, John P.
Abstract: Purpose: The purpose of experiment one was to determine the appetite, acylated ghrelin and energy intake response to breakfast consumption and omission in hypoxia and normoxia. Experiment two aimed to determine the appetite, acylated ghrelin and energy intake response to carbohydrate supplementation after both breakfast consumption and omission in hypoxia. Methods: In experiment one, twelve participants rested and exercised once after breakfast consumption and once after omission in normobaric hypoxia (4300 m: Fi O2 11.7%) and normoxia. In experiment two, eleven participants rested and exercised in normobaric hypoxia (4300 m: Fi O2 11.7%), twice after consuming a high carbohydrate breakfast and twice after breakfast omission. Participants consumed both a carbohydrate (1.2g·min − 1 glucose) and a placebo beverage after breakfast consumption and omission. Measures of appetite perceptions and acylated ghrelin were taken at regular intervals throughout both experiments and an ad-libitum meal was provided post-exercise to quantify energy intake. Results: Breakfast consumption had no significant effect on post exercise energy intake or acylated ghrelin concentrations, despite reductions in appetite perceptions. As such, breakfast consumption increased total trial energy intake compared with breakfast omission in hypoxia (7136 ± 2047 kJ vs. 5412 ± 1652 kJ; p = 0.02) and normoxia (9276 ± 3058 vs. 6654 ± 2091 kJ; p < 0.01). Carbohydrate supplementation had no effect on appetite perceptions or acylated ghrelin concentrations after breakfast consumption or omission. As such, carbohydrate supplementation increased total energy intake after breakfast consumption (10222 ± 2831 kJ vs. 7695 ± 1970 kJ p < 0.01) and omission (8058 ± 2574 kJ vs. 6174 ± 2222 kJ p = 0.02). Conclusion: Both breakfast consumption and carbohydrate supplementation provide beneficial dietary interventions for increasing energy intake in hypoxic conditions.